PT Company Profile Video Design. Charoen Pokphand Indonesia Medan - Prasasti; Sri Wahyuni Panjaitan (Formosa Journal of Applied Sciences, 2023)
The Indonesian company that focuses on agriculture is called PT. Charoen Pokphand Indonesia Tbk (CPI). PT Division. Charoen Pokphand Indonesia Tbk covers the fields of animal feed, animal husbandry and livestock processing. Very fast technical progress means that video media can also be used to convey information, apart from text and images. namely the company profile video. Company profile videos can be used as a means of promoting a product or service. Apart from that, company profile videos can also be used as a condition for participating in certain events such as exhibitions, exchanges, seminars and workshops. Based on the background of this problem, the author uses this title to conduct PT Design research. Charoen Pokphand Indonesia Medan Company Profile.